International environmental (in)justice: critical legal studies and justice in climate change - Adamian, Martin Joseph, author; MacDonald, Bradley J., advisor; Stevis, Dimitris, committee member; Betsill, Michele M., committee member; Trembath, Paul, committee member (Colorado State University. Libraries, 2006)
Most agree that severe climate change is now virtually inevitable, as is the widespread ecological destruction, extinction, and human suffering that will come with it. This study seeks to critically assess the prospect of achieving international environmental justice through the use of international law in climate change. In order to do so, I look at the significance of liberal theories of law and the ways in which strands of critical jurisprudence have drawn into question some of liberalism's fundamental assumptions. Concepts of social justice rooted in traditional liberal theory are not adequate for addressing the kinds of competing moral claims that have arisen over environmental issues. The role of community and culture is also not easily captured in traditional liberal theories of social justice because such theories, which are typically grounded in a concern for individual rights and preferences, do not recognize claims based on the value of group identity. Furthermore, the international legal system, much like our domestic legal systems, relies on a liberal orientation towards the role of law as a solution to problems such as environmental degradation. In this regard, the liberal assumptions about the rule of law, subjective values, and the problems with legislation and adjudication must be considered if we seek to achieve any kind of international environmental justice. The current international system was established around the idea of state sovereignty and reflects the hierarchies of power that have developed in that context. Ultimately, by showing the advantages of a critical legal approach I argue that liberal legal theory alone is insufficient for addressing the difficult and complicated issues that arise in regards to global environmental problems. As a result, a critical pluralist approach must be utilized in order to address problems such as climate change in a just manner.
Keywords: environmental science